Community-Based Disaster Mitigation: Knowledge and Social Capital in Reducing the Impact of Disaster - Purba, Ririn; Rusmiyati, Chatarina; Andari, Soetji; Suryani, Suryani; Ulil Absor, Muh. (KnE Social Sciences, 2022)
The National Disaster Management Agency reported that 383 out of 514 districts/municipalities throughout Indonesia are prone to natural disasters. Social capital is seen as one of the community strengths in disaster mitigation strategies. This study examined the model of community-based disaster mitigation, the level of knowledge and the social capital of the communities in disaster-prone areas in Semarang Municipality and Situbondo District. This study employed a mixed-methods approach, interviewing 120 respondents. We found that men had better knowledge of disaster mitigation than women. The involvement of men in awareness-raising about disaster mitigation activities was also higher than women. As a result, women are more vulnerable during a disaster. This study also found a variation in community understanding regarding disaster mitigation and social capital in the two locations. Respondents in Semarang, which is an urban community, reported a lower level of knowledge on disaster mitigation and social capital. Respondents from Situbondo reported higher social capital in four dimensions, including trust, norms, values, and networks. The geographical location and culture likely explain the variation. This reflects that urban areas are more vulnerable than rural areas in disaster mitigation. Keywords: community knowledge, disaster, mitigation, social capital